2014
DOI: 10.1177/0146167214530436
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Kill–Save Ratios Ease Up the Cognitive Demands on Counterintuitive Moral Utilitarianism

Abstract: The dual-process model of moral judgment postulates that utilitarian responses to moral dilemmas (e.g., accepting to kill one to save five) are demanding of cognitive resources. Here we show that utilitarian responses can become effortless, even when they involve to kill someone, as long as the kill-save ratio is efficient (e.g., 1 is killed to save 500). In Experiment 1, participants responded to moral dilemmas featuring different kill-save ratios under high or low cognitive load. In Experiments 2 and 3, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
2
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 20 publications
3
111
2
7
Order By: Relevance
“…Another drawback of the study is the limited number of moral dilemmas used, although this is not an unusual practice (e.g., Mendez et al, 2005; Gleichgerrcht et al, 2011, 2013; McIlwain et al, 2012; Trémolière et al, 2012; Gleichgerrcht and Young, 2013; Jack et al, 2014; Trémolière and Bonnefon, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another drawback of the study is the limited number of moral dilemmas used, although this is not an unusual practice (e.g., Mendez et al, 2005; Gleichgerrcht et al, 2011, 2013; McIlwain et al, 2012; Trémolière et al, 2012; Gleichgerrcht and Young, 2013; Jack et al, 2014; Trémolière and Bonnefon, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Disrupting cognitive processing by imposing cognitive load or by using noninvasive brain stimulation technique makes participants either slow down while endorsing utilitarian solutions (Greene et al, 2008) or makes it less likely that they will endorse utilitarian solutions (Trémolière et al, 2012; Conway and Gawronski, 2013; Jeurissen et al, 2014; but see Tassy et al, 2012). Easing up cognitive demands by using efficient kill-save ratios makes people more utilitarian (Trémolière and Bonnefon, 2014). Cognitively exhausting participants using sleep deprivation also increases response latencies while providing utilitarian moral judgments (Killgore et al, 2007; Tempesta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that outcomes might be more important than methods for moral judgements of other‐orientation lies. In addition, previous studies found that people would judge a behaviour to be more moral as the value of its outcome increases (Trémolière & Bonnefon, ). Therefore, if individuals perceived the outcome of an other‐orientation lie to be more important and valuable, they are more likely to judge the lie to be more moral.…”
Section: Message‐matching Effect and Processing Fluencymentioning
confidence: 97%
“…Greene et al [22] argue that these results provide evidence in support of their hypothesized asymmetry between utilitarian and deontological moral judgments, with the former driven by relatively more analytical thinking and the latter by relatively more intuitive thinking. Later studies [2325] have reported more direct evidence in support of a sequential dual process model, showing that putting subjects under cognitive load decreases utilitarian moral judgments. Moreover, Paxton et al [17] showed that subjects became more utilitarian when primed into reflective thinking by administering the Cognitive Reflection Task [26] prior to making the moral judgments.…”
Section: Introductionmentioning
confidence: 99%